2013
DOI: 10.1177/0300060513490617
|View full text |Cite
|
Sign up to set email alerts
|

Combined staining for immunohistochemical markers in the diagnosis of papillary thyroid carcinoma: Improvement in the sensitivity or specificity?

Abstract: The combination of HBME-1 and either CK19 or galectin-3 or HER-2/neu can improve the specificity of the diagnosis of PTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Some ancillary approaches (such as immunohistochemistry and molecular techniques) have been explored. [9] In our study, the highest frequency of cases (49.9%) was seen in 31-40 years of age group. These findings are in concordance with the studies done by Ramesh et al, [10] Wani et al [11] and Kolur et al [12] Wani et al and Ramesh et al analyzed that the relative peak incidence was seen in 30-39 years age group.…”
Section: Discussionsupporting
confidence: 47%
“…Some ancillary approaches (such as immunohistochemistry and molecular techniques) have been explored. [9] In our study, the highest frequency of cases (49.9%) was seen in 31-40 years of age group. These findings are in concordance with the studies done by Ramesh et al, [10] Wani et al [11] and Kolur et al [12] Wani et al and Ramesh et al analyzed that the relative peak incidence was seen in 30-39 years age group.…”
Section: Discussionsupporting
confidence: 47%
“…The reasons for the discrepancies in CK19 expression and postsurgical course of PTC are not epitope-1, have some significance in differentiating thyroid carcinomas and have been widely described [20,35,36]. However, their value as prognostic factors of the aggressive course of PTC has not been clearly established [2,20,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…However, their value as prognostic factors of the aggressive course of PTC has not been clearly established [2,20,[34][35][36]. Knowledge of high aggressiveness in PTC and the high probability of its early recurrence -even after early primary surgical treatment -may improve the effectiveness of further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have evaluated HER2 expression in thyroid cancer with controversial results, largely due to inter-study differences in the size and setting of the examined series and, most of all, to the subjective assessment and lack of uniform methodology [14,15,16,17,18,19,20,21,22,23,24,25,26]. Indeed, studies reported in the literature in the past several decades markedly differ by the methodological approach used to assess HER2 status [14,15,16,17,18,19,20,21,22,23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on HER2 have also been performed in thyroid cancer cells and tissues [14,15,16,17,18,19,20,21,22,23,24,25,26]. Interestingly, a wide variation in HER2 overexpression was reported in such studies, with positivity rates varying from 0% up to 70%, which may largely be attributed to inter-study technical and interpretive variations.…”
Section: Introductionmentioning
confidence: 99%